Laboratory Staff Communication and Patient Perception of Care: The Mediating Effect of Patient Understanding in Public Hospitals - Ruri Rizki Anriani; Hans Eldith Monintja; Innocentius Bernarto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Effective communication is a critical component of healthcare services, as it enhances patient understanding and shapes perceptions of care quality. Laboratory departments, as medical support units, interact directly with patients, particularly during the pre-analytical phase, making the quality of laboratory staff communication essential. This study aims to examine the effect of laboratory staff communication, represented by clarity and empathy, on patient perception of care, with patient understanding of laboratory procedure as a mediating variable. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 251 patients who received laboratory services at a Type C public hospital in Indonesia and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that empathy has a positive and significant effect on patient understanding of laboratory procedure, whereas clarity does not show a significant effect. Furthermore, clarity, empathy, and patient understanding of laboratory procedures significantly influence patient perception of care. These findings highlight that empathetic communication plays a key role in improving patient understanding, while communication clarity strengthens positive perceptions of laboratory service quality. This study provides practical implications for hospital management to enhance laboratory staff communication competencies as part of quality improvement strategies.